KONSEP MOTIVASI BELAJAR DI MASA PANDEMI COVID 19 - Siti Nafsiatul Hikmiyah; Hamam Burhanuddin (Pendidikan Agama Islam, 2020)
The Covid 19 pandemic has changed the education system in Indonesia, especially in the learning process, changes in the learning process will be an impact on the learning patterns as running face-to-face, also on student learning motivation. this research discribe the concept of learning motivation during the Covid 19 pandemic, using a literature review approach, which contains theories relevant to research problems, based on the available literature, especially from articles published in various scientific journals. The data collection using primary sources and secondary sources, analysis using content analysis techniques. As the results, the concept of learning motivation during the Covid 19 pandemic divided into two factors,Â students have high motivation due to student intelligence factors, student activity, the development of student learning independence, the existence of discipline, and learning is a fun activity. Low student motivation to learn is caused by low intelligence factors, excessive demands, weak discipline, stress, and learning is a tedious activity.